(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In the market economy, the result of all actions and activities is profit and loss. But it is better for firms and companies and organizations to benefit. The increase in profit is also in the interest of society, because the high profitability of economic activity leads to an increase in the national income of the whole country with an increase in individual profit. It can be said that the amount of profit and its level is the driving force of market participants, especially entrepreneurs. The interest of the market participant is determined by the amount of profit.